Calcul des sections efficaces et les taux d'ionisation pour l'hélium neutre et quelques ions héliumoïdes. - Nani, Baya (جامعة الوادي University of Eloued, 2019)
ملخص: التأين بواسطة التأثير الإلكتروني هو عملية ذرية أساسية في محاكاة الانبعاثات الإشعاعية للأشعة وأيضًا لدراسة التوازن الأيوني. تتطلب العديد من المشكلات المتعلقة بدراسة البلازما المخبرية والفيزياء الفلكية والانصهار النووي الحراري المتحكم فيه معرفة مسبقة بالهيكل الذري مثل طاقات المستويات المختلفة والمقاطع الفعالة. لقد استخدمنا، في عملنا هذا، معادلات شبه تجريبية لحساب المقاطع الفعالة للتأين لذرة الهليوم و الأيونات الشبيهة بالهليوم : Be+2 وLi+ . يتم حساب معدلات التأين من المقاطع الفعالة وموزونة بواسطة توزيع ماكسويلي.ABSTRACT: The electron impact ionization is an important atomic process in the simulation of line radiative emissions and also for the study of ion balance. Several issues related to the study of laboratory plasmas, astrophysics and controlled thermonuclear fusion require the knowledge of the atomic structure as the energies of different levels and cross sections. In our work, we used semi-empirical equations to calculate the ionization cross sections of Helium like and Li+ and Be+ 2 ions. Ionization rates are generated from the cross sections and weighted by a Maxwellian distribution.
مذكرة ماستر تخصص قيزياء
Keywords: المقاطع الفعالة، التأين بواسطة التأثير الإلكتروني ، دالة التوزيع الماكسويلي.; Cross sections, Electron impact ionization, Maxwellian distribution function.